PERBAIKAN USAHA PETERNAKAN SAPI PADA ASPEK PAKAN DI NAGARI SIGUNTUR, KECAMATAN SITIUNG, DHARMASRAYA - Ediset Ediset; Edwin Heriyanto; Amrizal Anas (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Community service in Nagari Siguntur, Sitiung District, Dharmasraya Regency aims to: 1) Increase the knowledge and skills of farmers about how to use agricultural waste such as fermented banana weeds as cattle feed and 2) Introduction of innovation technology in Urea Molases Block (UMB) feed as cattle feed. The method applied in this service activity is an extension method with a demonstration method approach, coaching and evaluation methods. The extension method demonstration approach was applied to banana weevil fermentation activities and during the introduction of innovation Urea Molases Block (UMB), while evaluation was carried out every one activity was completed and coaching would carried out continuously both directly and in remote discussions. The result of the service is knowledge and skills of breeders increase on the aspect of feed, especially alternative feeds such as Banana Bifold Fermentation (BBF) and feed Urea Molasses Block (UMB). Other results from this activity can also be seen from the high response of cattle farmers in Nagari Siguntur to each stage of the activities carried out, with evidence of the number of farmers who attended and who asked quite a lot at the time of the activity and besides each activity was attended by Nagari officials and officers Dharmasraya District extension agent. Service activities for farmers can change the behavior of cattle farmers, both in the aspects of knowledge, attitudes and skills that local extension officers should be able to carry out extension activities consistently and accompanied by academics as resource persons.